Controle direto de torque para uma máquina de indução eneafásica com redução de correntes harmônicas - Paz, Gilielson Figueredo da (2020)
Electric induction machines are responsible for much of the driving force of industrial environments worldwide, being the largest representation in the energy consumption matrix of Brazilian industries. This strategic position highlights research in improving the development of machines and robust drive techniques that bring energy and financial savings. In this context, multiphase induction electric machines have stood out over the years in specific applications such as propulsion of ships and electric vehicles, elevators and aircraft. Some advantages presented by these machines that motivated the increase in research are: high efficiency, fault tolerance, higher power density and greater reliability. For this reason, the development of variable speed drive techniques, such as direct torque control (DTC), for multiphase machines is essential. The DTC has simplicity of implementation, robustness and less computational effort. This work discusses a method of direct torque control that uses virtual voltage vectors to reduce the harmonic distortion of the phase current in a symmetric induction drive system. As the classic DTC is a direct adaptation of the three-phase control, it does not take into account the presence of harmonic current components obtained from the spatial vector decomposition technique (SVD). Thus, in the classic DTC, these harmonic current components assume high amplitudes, causing distortion in the phase currents. In this way, it is shown that the DTC with virtual vectors minimizes the unwanted components, significantly reducing the distortion in the phase currents, maintaining the fast dynamic response of the classic DTC.